Re-recognizing micro locations of nanoscale zero-valent iron in biochar using C-TEM technique - Kun Yang (Nature Portfolio, 2021)
Abstract Biochar supported nanoscale zero-valent iron (NZVI/BC), prepared commonly by liquid reduction using sodium borohydride (NaBH4), exhibits better reduction performance for contaminants than bare NZVI. The better reducing ability was attributed to attachment of nanoscale zero-valent iron (NZVI) on biochar (BC) surface or into the interior pores of BC particles due to observations by scanning electron microscopy (SEM) and plan transmission electron microscopy (P-TEM) techniques in previous studies. In this study, cross-sectional TEM (C-TEM) technique was employed firstly to explore location of NZVI in NZVI/BC. It was observed that NZVI is isolated from BC particles, but not located on the surface or in the interior pores of BC particles. This observation was also supported by negligible adsorption and precipitation of Fe2+/Fe3+ and iron hydroxides on BC surface or into interior pores of BC particles respectively. Precipitation of Fe2+ and Fe3+, rather than adsorption, is responsible for the removal of Fe2+ and Fe3+ by BC. Moreover, precipitates of iron hydroxides cannot be reduced to NZVI by NaBH4. In addition to SEM or P-TEM, therefore, C-TEM is a potential technique to characterize the interior morphology of NZVI/BC for better understanding the improved reduction performance of contaminants by NZVI/BC than bare NZVI.